POTENTIAL ANTIGENTS FOR MALARIA VACCINE: A NEW HOPE FOR MALARIA ELIMINATION - MUHAMMMAD, ISMAIL; PUKUMA, M. S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
Malaria is a dangerous mosquito-borne disease caused by Plasmodium parasite. The disease threatens more than half of the world’s population. Malaria prevention and treatment rely on synthetic medications, but the parasites have evolved resistance to all classes of drugs advised. This, together with the high prevalence of malaria in the developing world, highlights the urgent need for vaccine development. The purpose of this paper was to review the current level of knowledge on various Plasmodium antigens that can elicit the appropriate immune response. Several malaria vaccine candidates are moving forward, with more than 30 in advanced preclinical or clinical phases of development. However, only the RTS,S/AS01 vaccine has completed Phase III testing and got a favourable regulatory assessment. Pre-erythrocytic Vaccines (PEVs), Blood-Stage Vaccines (BSVs), and Transmission-Blocking Vaccines are the three types of malaria vaccines (TBVs). The majority of PEV research is currently focused on the development of subunit vaccines against parasite proteins such as the Pf circumsporozoite protein (PfCSP), the thrombospondin-related adhesion protein (TRAP), and the liver stage antigen (LSA). BSVs attack the parasite’s blood stages. Two of the most likely BSV candidates are P. falciparum merozoite surface protein-1 (PfMSP1) and P. falciparum Apical Membrane Antigen-1 (PfAMA1). The most advanced contender is Plasmodium falciparum Reticulocytebinding protein homolog 5 (PfRH5). TBVs interfere with the parasite’s sexual development in the vector. Pfs25, P230, P48/45, Pfs2400, Pfg 27, Ps28, and Ps21 proteins are powerful antigens in TBVs because they are found at various phases of the parasite’s growth while in the mosquito. With the availability of many various antigens, a malaria vaccine could be developed in the near future. More study into the practical application of these antigens is needed in order to produce a malaria vaccine quickly.